1991
DOI: 10.1002/macp.1991.021920819
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural studies of new copolyimides 2. Influence of pyromellitimide rings on copolymer structure

Abstract: The reaction of pyromellitic dianhydride (1,2 : 4,5-benzenetetracarboxylic dianhydride) (1) with L-and D-alanine ( 2~) and ( 2~) leads to new monomers which were used to synthesize new copolymers. These copolymers were obtained as a product of the condensation of optical isomers of bis[N-(1 -chloroformylethyl)]pyromellitimides (CFEP) with poly(ethy1ene glycol) PEG-2000 (5). The effect of monomer structure on the structure and thermal properties of the polymers was studied using X-ray diffraction, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
3
0
2
Order By: Relevance
“…In the first step, TMI-GTAn which was a precursor of TMIAc-GTAn, was obtained by a condensation reaction of TMA with L-glutamic acid 11) . In the second step, TMIAc-GTAn was synthesized by treatment of TMI-GTAn with excess thionyl chloride [5][6][7] . In detail, TMI-GTAn was synthesized from the reaction of trimellitic anhydride with glutamic acid as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first step, TMI-GTAn which was a precursor of TMIAc-GTAn, was obtained by a condensation reaction of TMA with L-glutamic acid 11) . In the second step, TMIAc-GTAn was synthesized by treatment of TMI-GTAn with excess thionyl chloride [5][6][7] . In detail, TMI-GTAn was synthesized from the reaction of trimellitic anhydride with glutamic acid as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, those have better solubilities than polyimides containing pyromellitimide and glutamimide units or the representative PAI, Torlan 11) . It was reported that the aromatic-aliphatic poly-(iminoamic acid)s prepared from N-(pyromellitimino) diglutamic anhydride have excellent storage stabilities either in solution or in solid state in contrast to the aromatic poly-(amic acid)s prepared from pyromellitic anhydride [4][5][6][7]11) . This is also expected in case of PAIIs described in this report.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Syntezy prowadzono w zestawie aparaturowym sk³adaj¹cym siê z okr¹g³odennej kolby trójszyjnej zaopatrzonej w mieszad³o mechaniczne, ch³odnicê zwrotn¹, termometr oraz p³aszcz grzejny. Pos³u¿ono siê czterema metodami, opracowanymi na podstawie danych literaturowych dotycz¹cych podobnych syntez [11][12][13].…”
Section: Otrzymywanie Optycznie Czynnych Kwasów Dikarboksylowych Z Ugunclassified
“…Dostêpna literatura zawiera niewiele tylko doniesieñ odnosz¹cych siê do optycznie czynnych PI. Pojedyncze publikacje dotycz¹ optycznie czynnych poli(eteroimidów) otrzymywanych z optycznie czynnego dibezwodnika 2,2'-bis(3,4-dikarboksyfenoksy)-1,1'-binaftalenowego oraz amin aromatycznych w typowej dwuetapowej metodzie obejmuj¹cej reakcjê polikondensacji i cyklodehydratacjê [10], a tak¿e optycznie czynnych poli(estroimidów) uzyskiwanych z glikolu polioksyetylenowego oraz produktów reakcji bezwodnika piromelitowego i D-oraz L-alaniny [11].…”
unclassified